(untitled) (Eurasian Scientific Herald, 2022)
The presented article presents innovative methods aimed at developing the motor abilities of young boxers. The types of simple motor reactions used in the training process of young boxers have been studied in detail. Studied methodical approaches in the development of power abilities representing the main base at the stage of sports improvement.